Strength and conditioning for field hockey - Hudson, A. (Strength and conditioning for sports performance, 2016)
An effective approach is to influence the quality of the performance by working with the coaches to find a wav to win. This is different to just developing a physical characteristic based on the general needs of the sport. In order to get the thought process the right way round you really have to work on understanding hockev as a sport, as well as what your technical coaches are trying to achieve.